Preemptive oral paracetamol in laparoscopic cholecystectomy surgery - a comparative study - Saha, Nepal Chandra; Masud, Mehedi; Sofiuddin, Mohammad; Rahman, Mushifqur; Bhowmick, Dilip Kumar; Akhtaruzzaman, AKM (Journal of the Bangladesh Society of Anaesthesiologists, 2014)
Background Laparoscopic cholecystectomy causes a considerable pain in the post operative period. Preemptive use of oral paracetamol decreases the intensity of pain and subsequently reduces the dose of opioid as well as nausea and vomiting. Objective The study was designed to observe the effect of preemptive oral paracetamol reduces the dose of postoperative opioid and nausea and vomiting. Methods Fifty patients of ASA physical status I and II, age range 16-50 years and BMI 18.5-24.9 were randomly selected by cards sampling method. They were equally divided into two groups of 25 patients in each group. Group I received vitamin, Group-II received 1 g oral paracetamol 60 min before surgery. In the recovery room dose of opioid was measured in 1, 6, 12, 24 hours and frequency of nausea, vomiting were assessed. Results The total amount of pethidine needed significantly lower in the case group than that in the control group (p = 0.012). The pain scores were comparatively low in case group than that in the control group from beginning to endpoint of evaluation following operation (p = 0.027). The complaint of nausea at 6 and 12 hours was much less in the case group than that in the control group. Majority (80%) of patients in control group demanded analgesic (pethidine) 10 minutes earlier after operation as opposed to only 8% of the control group (p = 0.014). Conclusion Preemptive paracetamol reduces the intensity of postoperative pain and requirements of pethidine to a large extent with no significant side effects. DOI: http://dx.doi.org/10.3329/jbsa.v26i1.19814 Journal of Bangladesh Society of Anaesthesiologists 2013; 26(1): 33-38